Subsidies as an Instrument in Agriculture Finance : A Review - Meyer, Richard L. (World Bank, Washington, DC, 2013)
This paper presents a literature review of issues related to recent subsidies and investments in the financial sector that have been designed to address the immediate effects of the crises and to develop the financial institutions necessary to modernize agriculture. Section two of the paper discusses the impact of recent food, fuel, and financial crises on developing countries and the emergency actions taken by countries and international agencies to reduce the suffering inflicted on poor people. It also discusses the challenge of finding a balance between pragmatic immediate responses and longer-term objectives. The third section discusses the role of finance in agricultural development and poverty alleviation. Section four deals with the challenge of creating credit markets in developing countries. The fifth section covers shifts in the paradigm used to intervene in credit markets and summarizes the main features of the old directed-credit and the new financial systems paradigms. This is followed by a sixth section that summarizes highlights in the development of the microfinance industry. It covers guidelines created for developing microfinance, microfinance penetration into rural areas and agriculture, innovations and prospects for future agricultural lending, and insights gained about the impact of finance on poor households. The seventh section addresses topics related to the demand for credit, including rates of return earned in agriculture and in microenterprises, and research results analyzing sensitivity of loan demand to interest rates. Section eight describes major interventions by international agencies and points the way forward for agricultural credit. It reviews the debates about the use of grants and subsidies, especially in the food, fertilizer, and credit markets, and the rationale for smart subsidies. It then describes experiences in five major areas of international agency activities: micro-insurance and weather-index-based insurance, credit guarantee funds, warehouse receipts, specialized agricultural development banks, and agricultural investment funds. Section nine summarizes the main conclusions based on literature consulted for this review. It identifies major lessons learned with suggestions for priorities that Improving Capacity Building in Rural Finance (CABFIN) members might consider supporting in their projects and programs.